Stress–strain partitioning behavior and mechanical properties of dual-phase steel using finite element analysis. (December 2020) - Maeda, Ryotaro; Wang, Zhi-Lei; Ogawa, Toshio; Adachi, Yoshitaka
Abstract: Various industrial applications require materials with both high strength and good ductility. However, strategies for enhancing material performance are usually trapped in a strength–ductility trade-off. In this study, the effect of martensite morphologies (including geometry, connectivity, and distribution direction) on the stress–strain partitioning behavior and mechanical properties of a ferrite-martensite dual phase steel was studied using the secant method and finite element analysis. The results demonstrated that the combination of rhombus and horizontal geometries provided a good balance of strength and ductility. Thus, a combination of 45° and 0° regarding the angle between the directions of martensite distribution and deformation was further determined to be beneficial to the strength–ductility balance. These results are expected to provide a general understanding of strengthening and toughening mechanisms and will promote the development of high-performance steels.